2012
DOI: 10.3998/jmmh.10381607.0006.205
|View full text |Cite
|
Sign up to set email alerts
|

“Thinking Too Much”: Psychological distress, sources of stress and coping strategies of resettled Afghan and Kurdish refugees

Abstract: This article outlines the main findings of an exploratory, mixed methods study examining the health and resettlement experiences of predominantly Muslim Afghan and Kurdish refugees in New Zealand and Australia. As post-migration experiences can impact the psychological well-being of already traumatized individuals, this study aimed to identify major sources of stress and describe the coping strategies they use to deal with it. Spending too much time reflecting on past experiences and current international even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
43
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 50 publications
7
43
2
Order By: Relevance
“…Eight quantitative studies were eliminated on grounds that prevalence rates for outcomes of interest were not specifically reported for Afghans [72–79]. Of the 23 remaining studies, two were mixed-method [80, 81], nine qualitative [3, 8289], and 12 quantitative [90101]. One quantitative study [95] was published in the Dutch language; however, the articles’ English language abstract provided relevant information with relation to answering our second research question, and was therefore retained in our final sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight quantitative studies were eliminated on grounds that prevalence rates for outcomes of interest were not specifically reported for Afghans [72–79]. Of the 23 remaining studies, two were mixed-method [80, 81], nine qualitative [3, 8289], and 12 quantitative [90101]. One quantitative study [95] was published in the Dutch language; however, the articles’ English language abstract provided relevant information with relation to answering our second research question, and was therefore retained in our final sample.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were combined as they essentially used the same sample in separate publications. These combinations were as follows: one mixed-method [81] and one quantitative (validation) study [101] (the other mixed-method study [80] was later eliminated as findings were reported for only a subset (one-third) of the entire sample); four qualitative studies [3, 85, 87, 88]; and four quantitative studies [90, 91, 98, 99]. This subsequently resulted in a total sample size ( n ) of 17 studies (one mixed-method, seven qualitative, nine quantitative).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations